2013
DOI: 10.1108/bepam-04-2012-0014
|View full text |Cite
|
Sign up to set email alerts
|

Can the pilot public-private partnerships project be applied in future urban rail development?

Abstract: Purpose – This purpose of this paper is to evaluate the experiences of public-private partnerships (PPPs) in China's urban rail development, investigates the critical factors impacting on the project viability and derives lessons for future urban rail PPP projects in China and elsewhere. Design/methodology/approach – A case study of the Beijing Metro Line 4 project was adopted as the main research method with semi-structured interviews with senior practitioners and experienced academics as the primary dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…For instance in the water sector, Meng et al (2011) investigated into the CSFs for PPP water projects in China which is of a transfer operate transfer model. Likewise other infrastructure sectors of which PPP has been implemented have their CSFs explored and these include the transportation, telecommunication, energy and housing sectors (Liu and Wilkinson, 2013; Abdul-Aziz and Kassim, 2011; Askar and Gab-Allah, 2002; Jamali, 2004;Ozdoganm and Birgonul, 2000).…”
Section: Critical Success Factor Model In Previous Ppp Studiesmentioning
confidence: 99%
“…For instance in the water sector, Meng et al (2011) investigated into the CSFs for PPP water projects in China which is of a transfer operate transfer model. Likewise other infrastructure sectors of which PPP has been implemented have their CSFs explored and these include the transportation, telecommunication, energy and housing sectors (Liu and Wilkinson, 2013; Abdul-Aziz and Kassim, 2011; Askar and Gab-Allah, 2002; Jamali, 2004;Ozdoganm and Birgonul, 2000).…”
Section: Critical Success Factor Model In Previous Ppp Studiesmentioning
confidence: 99%
“…Most risks related to commissioning, operation, and maintenance were transferred to the private sector, whilst the government undertook or shared risks which were beyond the control of the private sector (Roumboutsos, Liu and Wilkinson, 2013). For instance, the public sector shared the construction risk by dividing it into two parts and undertaking Part A with riskier civil works; the government also used shadow patronage, that is a means to compensate the private partner, against the risk of lower ridership than projected.…”
Section: Private Involvementmentioning
confidence: 99%
“…Yuan et al (2010) identified 15 driving factors associated with PPP projects in metropolitan transportation systems from the perspective of Chinese public sector; de Jong et al (2010) studies seven urban rail PPP projects in five large metropolitan areas in China; Roumboutsos, Liu and Wilkinson (2013) evaluated the experience of PPPs in China's urban rail development with the focus on critical factors impacting on the project viability based on a case study of Beijing Metro Line 4; Chang (2013) also studied the Beijing Metro Line 4 to illustrate benefits, costs, opportunities and risks in PPPs in China, and he later studied the Beijing metro financing sustainability to demonstrate how subnational governments finance the investment in metro systems (Chang, 2014).…”
Section: Ppp Research In Urban Rail Transportation In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Kanter (1999) considers investment by both parties (public and private) essential to ensure full commitment when analysing PPP projects in the social sector. Liu and Wilkinson (2013), based on the case study of the Beijing Metro, found that government involvement through revenue subsidies would be essential to implement urban rail PPP projects that are viable from the financial standpoint. Finally, multilateral support has proven to be effective in lowering both the cancellation rate and the likelihood of distress of PPP projects (Jandhyala, 2016;Marcelo and House, 2016).…”
Section: Analysis Of the Impact Of Public Support At The Project Levelmentioning
confidence: 99%